Double right coronary artery and its clinical implications. (5th March 2013) - Chien, Tsu-Ming; Chen, Chih-Wei; Chen, Huai-Min; Lee, Chee-Siong; Lin, Ching-Cheng; Chen, Ying-Fu
Abstract: Congenital anomalies of the coronary arteries are present in 0.2–1.4% of the general population. These anomalies represent one of the most confusing issues in the field of cardiology and challenges for interventional cardiologists and cardiac surgeons if the anomalies are unrecognised. Double right coronary artery is one of the rarest coronary arteries. Previously, the probability of developing atherosclerotic changes in patients with a double right coronary artery was considered to be equal to that in those without it. In reality, however, a high prevalence of atherosclerotic coronary artery disease was found in patients with a double right coronary artery originating from a single ostium after our comprehensive literature search through the PubMed database. Owing to the fact that double right coronary artery is both a congenital and potentially atherosclerotic coronary artery disease at diagnosis, coronary intervention or cardiac operation is more complicated than previously believed. Individuals with a double right coronary artery may be unaware of its presence until an accidental finding during coronary angiography or cardiac operation and are at risk for unsuspected complications of atherosclerotic coronary artery disease or during cardiac operation. Therefore, it is important to obtain information on the anatomic variants of this congenital coronary anomaly in patients who are undergoing either coronary intervention, aortic root operation or myocardial revascularisation. To our knowledge, this is the first comprehensive article to discuss the anomalies and their clinical implications.